MODEL PEMBELAJARAN “TALAQQI” TAHFIDZUL QUR’AN ERA PANDEMI VIRUS CORONA 2019 (COVID 19) PADA SISWA GANGGUAN LAMBAT BELAJAR (SLOW LEARNER) SEKOLAH MENENGAH PERTAMA - Dirgayunita, Aries (Milenial, 2022)
This research is motivated because we all know that a child's religious education is not only influenced by the role of parents in educating and instilling spirituality (religion). What is meant by social is the culture that surrounds a child's life which is one of the major influences on life. The culture referred to in this case is the existence of customs in an area that is able to influence the moral or spiritual personality which is more specifically for Muslim minority children in areas where the majority are non-Muslims (Hindu). So this research has the aim of knowing the role of parents and religious culture in fostering the intelligence/spiritual abilities of Islamic minority children in Wonokerso Village, Sumber District, Probolinggo Regency. The data in this study were collected using the method of observation or observation, interviews or interviews and archiving data through documentation. Random Sampling Technique Data analysis technique is multiple correlation used to select samples. From the results of the analysis of the data obtained, it was found that parents have an important role in fostering and shaping the spirituality of children in the family in Wonokerso, Sumber District, Probolinggo Regency. So the religious values ??obtained by children can be taught and instilled through religious education that has been carried out according to Islamic religious rules, even though the values ??of religious education for children in Wonokerso Village based on data are not optimally received by them.